The South African Constitution as Memory and Promise: An Exploration of Its Implications for Sexual Violence. (2nd January 2016) - Du Toit, Louise
ABSTRACT: This article considers the South African Constitution as a living text that founds the new democratic state and asks about its politics of memory. By its very nature, a constitution looks simultaneously backwards and forwards: the promise of the constitution cannot be understood separately from its memory of the apartheid past, and vice versa. The past continuously gets rewritten and reframed as we always reinterpret it anew in light of current concerns and power distributions. It is argued that these politics do not fade away but rather intensify as we move further away from the constitutional moment in time. Focusing on the urgent problem of on-going very high levels of sexual violence in South Africa, the article tries to capture the ways in which constitutional memory and promise function and should function in this respect. Two strategies of memory, namely the memorial and the monumental, are distinguished and applied to the constitutional promise to end sexual violence.